Etiology of Total Knee Arthroplasty Failure and Functional Outcome of Revision Knee Arthroplasty. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the aetiology of total knee arthroplasty (TKA) failure and assess the functional outcome of patients who underwent revision total knee arthroplasty.Methods: It was a descriptive study conducted in Orthopaedic department Aga khan university hospital Karachi from 3rd Jan 2010 to 25th December 2020. All patients with primary total knee replacement who underwent revision total knee arthroplasty were included in this study. The indications for revision arthroplasty were documented. Functional outcome of revision total knee arthroplasty was assessed at 6 months with Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire. The preoperative and post operative WOMAC score were compared with Student-t test an P value calculated. P value